Do we have the spark? - Rupel Valentina Prevolnik; Marušič Dorijan (Sciendo, 2022)
Upgrading any system is challenging. Neglecting continuous monitoring and evaluation might impose solutions that worsen the situation. Primary orientation toward increasing productivity is the main reason for the tremendous decline in the accessibility of outpatient services in Slovenia since 2015, in addition to additional funds from the state budget. In the actual 'fee-for-service', providers are incentivised to deliver more expensive services, not first visits. Although the stakeholders are not to blame, it is high time for an orientation towards patients' needs: a breakaway from inefficient technical solutions, an acceptance of patients as active participants in decision-making, measurement of their treatment outcomes, and the adoption of already proven advanced payment models, such as population-based payments. The journey towards value-based healthcare must start!